Continuous renal replacement therapy with adsorbing filter oXiris in the treatment of sepsis associated acute kidney injury: a single-center retrospective observational study - Feng Zheng; Yi-lan Wang; Wei-yi Zhou; Jing Zhang; Min Lu; Ni-fang Pan; Jian He; Qian Zhang; Lan Cao; Jiang-song Wu; Yan Gu; Li-hua Qiu; et al. (BMC Nephrology)
Abstract Background and objective Critical bedside ultrasound is widely used in clinical practice, and it can monitor renal perfusion. The reduction of renal perfusion and inflammatory injury are two contributing factors to sepsis-associated acute kidney injury (SA-AKI).The aim of this study was to examine whether the oXiris filter was useful in the continuous renal replacement therapy(CRRT) treatment of SA-AKI patients. Design, setting, participants, and measurements We performed a retrospective single-center observational study and enrolled two hundred and forty-three SA-AKI patients from January 2022 to December 2023, who were divided into the oXiris group (n = 88) and the control group (n = 155). The primary endpoints were the 28-day recovery of renal function and 28-day all-cause mortality. The secondary endpoints included renal Doppler markers (RRI, RVSI, and PDU), SOFA, vasoactive-inotropic score (VIS), inflammatory markers (PCT, CRP, IL-10 and TNFα), lactate level, and length of stay in ICU and hospital. Results For the primary endpoint, the rates of complete recovery, partial recovery, and dialysis dependence were observed to be 60.3%, 13.6%, and 26.1% in the oXiris group, respectively, compared to 63.9%, 15.5%, and 20.6% in the control group. The 28-day all-cause mortality was not different in the two groups (22.7% vs. 27.1%). For the secondary endpoint, the oXiris group exhibited greater reductions in VIS scores compared to the control group within the first 24 h (p = 0.001) and 48 h (p < 0.001) of CRRT. Following 48-h of CRRT, lactate levels in the oXiris group were significantly lower than those in the control group (p = 0.014). Prior to CRRT, levels of IL-6 were higher in the oXiris group (p = 0.036), but these differences were not significant after CRRT (p > 0.05). The levels of RRI at T1 (p = 0.002) and T2 (p = 0.001) were lower in the oXiris group than in the control group. Even after adjusting for AKI stage, multivariable Cox regression analysis showed that SOFA and inflammatory factors (TNFα, IL-10, and IL-6), oXiris were significantly associated with a lower 28-day mortality among SA-AKI patients when compared to M150 [HR = 0.466, 95%CI 0.233–0.934, p = 0.031]. Conclusion Our findings suggest that the use of the oXiris filter in CRRT is associated with reduced inflammatory injury and improvement in renal perfusion. However, it is not associated with improved 28-day recovery of renal function and 28-day all-cause mortality.